Edukasi Kesehatan pada Masyarakat Desa Dorang sebagai Mitigasi Bencana Banjir: Health Education for the Dorang Village Community as Flood Disaster Mitigation - Sari, Fariza Yulia Kartika; Septiani, Septiani; Khoiriyah, Nur (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Floods are one of the disasters with the highest incidence in Indonesia. In the last ten years, Dorang Village has experienced five floods. Health problems are one of the most obvious impacts caused by floods. Skin diseases, diarrhea, respiratory tract infections, and fever due to decreased immunity are some of the health problems that often arise in flood disaster conditions. The purpose of this community service is to educate about diseases caused by floods. In addition, identifying the factors cause these diseases to arise and how to prevent them. Increasing knowledge about health problems caused by floods is expected to minimize various health problems that occur in communities affected by floods. This health education activity is divided into three stages, namely the pre-service stage, health education, and activity evaluation. Evaluation of this education activity is carried out using a pre-post test. The pre-post test questions consist of 5 questions about the types, impacts, and how to prevent infectious diseases. In terms of types of contagious diseases, partner knowledge increased by 85% after being given education. The results of this increase also occurred in other aspects, namely the aspects of the impact and control of infectious diseases. Partner knowledge increased to 80% for the aspect of the impact of infectious diseases and increased to 75% for the aspect of managing participant diseases.